Utilisation of audible steganography to organise and analyse the text within WAV files. (5th February 2023) - Ramyadevi, R.; Poornima, V.
This project seeks to encrypt audio cover files and create temporal domain audio steganography, an audio file with hidden options and text. The mean square error (MSE), mean absolute error (MAE), signal-to-noise ratio (SNR), and cross-correlation analysis identify audio stream text data by comparing 8-bit and 16-bit pulse-code modulation (PCM) audio. This study estimates how many characters can be added to an audio file without changing its structure. MP3's bit rate is audible. Audio steganography is a secure, cost-effective approach to encrypting network data. It's useful for steganography due to low noise distortion. Undetectable embedding is preferable. The suggested technique improves accuracy at low embed levels, according to testing. The suggested strategy delivers the highest peak signal-to-noise ratio (PSNR) with hidden information in the first, second, and third least-significant bit (LSBs). Three LSB had 98% accuracy and the lowest false alarm rate (less than 5%). Experiments reveal that this study's method extracts audio. The recommended method is hard and capable. Novel audio file steganography is imperceptible and recovers messages, and text message length affects robustness.